Perspectives for and obstacles to energy democracy in renewable energy transition processes - Puczko, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The paper is an attempt to show both opportunities and limitations for energy democracy, which also multiplies the ambiguity of this concept, arising from the lack of coherent legal regulations. This means that, the perspectives that energy democracy opens can simultaneously be the barriers to its development. This results in a different social perception of this phenomenon, which affects legislation and effectiveness of forms of democratic participation in energy policy.
Keywords: energy democracy; energy transition; social movement; participation; renewable energy